2014
DOI: 10.1007/s00246-014-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Hepatic Biopsy in Stable Fontan Patients Undergoing Cardiac Catheterization

Abstract: Liver pathology complicates Fontan palliation. Previous reports established that both hepatic sinusoidal and portal fibrosis occur in patients after Fontan procedures. Past studies predominantly included symptomatic patient cohorts. Thus, the authors of this study aimed to characterize hepatic pathology via transvenous hepatic biopsies in 21 asymptomatic patients at the time of elective cardiac catheterization. Seven of these patients (33 %) were accompanied by an interventional procedure. Hepatic biopsies sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Previous reports describe portal and sinusoidal hepatic fibrosis even in asymptomatic Fontan patients [2,11]. Recently, we reported an association between hepatic total-fibrosis scores and postoperative Fontan patients with and without a history of obstructed pulmonary blood flow at birth [3].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous reports describe portal and sinusoidal hepatic fibrosis even in asymptomatic Fontan patients [2,11]. Recently, we reported an association between hepatic total-fibrosis scores and postoperative Fontan patients with and without a history of obstructed pulmonary blood flow at birth [3].…”
Section: Introductionmentioning
confidence: 70%
“…If the two pathologists scored a specimen feature differently, then they conferred to arrive at a final score. For each patient, we added the portal-fibrosis score to the sinusoidal fibrosis score for a total-fibrosis score (0-8) [2].…”
Section: Methodsmentioning
confidence: 99%
“…Two pathologists specializing in hepatology (SG and TCS), who were blinded to patient data, independently reviewed liver biopsy specimens. Portal fibrosis was graded using the Ishtak (stages 0–6) and Scheuer staging (stages 0–4) systems; and sinusoidal fibrosis was determined using staging described by Schwartz et al 12,13 Total fibrosis score was calculated by combining the grades of staging of all three staging techniques.…”
Section: Methodsmentioning
confidence: 99%
“…However, the risk factors for hepatic fibrosis remain unclear. We previously reported results of hepatic biopsies in stable Fontan surgery patients, and we found that fibrosis scores tended to moderately correlate with time from Fontan surgery [6]. Others have suggested thrombocytopenia as a marker for significant liver pathology [23].…”
Section: Introductionmentioning
confidence: 55%
“…Others have suggested thrombocytopenia as a marker for significant liver pathology [23]. Nevertheless, there are few reports that have analyzed hepatic biopsy findings in cohorts of either symptomatic or asymptomatic Fontan patients [6,14,16,23,24]. In lieu of liver biopsies, noninvasive magnetic resonance imaging and elastography, computed tomography, and ultrasound elastography all have enhanced the understanding of liver pathology and have identified elevated Fontan pressure, decreased cardiac index, elevated ventricular end-diastolic pressure, decreased ejection fraction, and elevated pulmonary arterial wedge pressure as risk factors for hepatic stiffness, which correlates with hepatic fibrosis from biopsy [3,9,17,28,29].…”
Section: Introductionmentioning
confidence: 99%